Modelos cosmológicos na teoria de Rastall - Mahamadou, Hamani Daouda (2012)
Rastall's theory is a modification of the general theory of relativity that leads to an expression different from the usual for the law of conservation in the field of matter. Recently it has been argued that such a theory may have applications to the problem of energy, since a fluid without pressure can lead to the acceleration of the universe. In this work, we confront Rastall's theory with the power spectrum data. The results indicate a configuration that essentially reduces Rastall's theory to general relativity, unless the unusual conservation law refers to a scalar field, a situation where other configurations would eventually be possible. A unification of energy dark and dark matter, is obtained if a wide field of non-canonical interaction, inspired by Rastall's theory of gravity, is imposed. In this case, agreement with the background tests and with the power spectrum is possible. We investigated the evolution of the gravitational potential in Rastall's scalar field theory. For a single component model, the perturbation theory, in Newtonian caliber, is consistent only for ? = 1, which is the limit of general relativity. On the other hand, it is possible to have a consistent model with ? 6 = 1 when another component, in the form of a perfect fluid, is introduced. We introduced in this theory a model of two fluids, one of the components representing the energy of the vacuum and the other the matter without pressure (for example, baryons plus matter is cold). The cosmological scenario is the same as for the ?CDM model, at the bottom and at the linear perturbative level, with the exception of one aspect: now the energy can be agglomerated. We hope that this may lead to the possibility of distinguishing the Rastall model from the ?CDM at a non-linear disturbing level